Revolutionizing Uzbekistan's Banking Sector Through Fintech Innovations: Mengubah Revolusi Sektor Perbankan Uzbekistan Melalui Inovasi Fintech - Ulmasov , Azizjon Sobirjonovich (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of fintech integration on Uzbekistan's banking sector, against the backdrop of the nation's economic transition towards diversification. Utilizing data analysis, we examine trends in QR-online transactions to uncover shifting consumer behaviors and the strategic implications for banking operations. Findings suggest a significant opportunity for banks to capitalize on digital payment solutions, with implications for enhancing operational efficiency and fostering financial inclusion. The study underscores the importance of proactive engagement with fintech innovations to drive sustainable growth and competitiveness within Uzbekistan's evolving financial landscape. Highlights: Digital Payment Potential: QR-online transaction analysis reveals opportunities for banks to leverage fintech for enhanced efficiency. Strategic Engagement: Proactive fintech adoption can drive sustainable growth in Uzbekistan's evolving financial landscape. Financial Inclusion Drive: Embracing digital solutions fosters accessibility, aiding in the inclusion of underserved populations. Keywords: Fintech, Banking Sector, QR-Online Transactions, Consumer Behaviors, Financial Inclusion